Analyzing Railway Passenger Satisfaction Using SERVQUAL and Importance- Performance Analysis (IPA) for Tourism Purposes - Kamila Syifa Ardiani; Fikri Fahru Roji; Ghaida Farisya (Badan Penerbit STIEPARI Press, 2025)
This study aims to analyze passenger satisfaction with the quality of railway services at Garut Station using the SERVQUAL method and the Importance Performance Analysis (IPA) approach. The research was conducted quantitatively through a survey of 102 respondents who used PT KAI services at Garut Station for tourism purposes. Data analysis was carried out by calculating the gap between passengers’ expectations and perceptions, and mapping service priorities using IPA with the assistance of SPSS 26 software. The results indicate that overall service performance has not met passenger expectations, particularly due to negative gaps in the dimensions of responsiveness, assurance, and empathy. However, there were positive gaps in the dimensions of tangibles and reliability. The accuracy of train departure and arrival schedules was identified as the top priority for improvement. These findings provide strategic recommendations for PT KAI to enhance service quality with a focus on customer satisfaction.